The Subjective Well-Being of the Staff at a Teaching Dental Center in a COVID-19 Epidemiological Surveillance System between the Years 2020 and 2022 - Corituma-Basaldua, Fabiola Antonella; Negrón-Saldaña, Lucía Rafaela; Rojas-Susanibar, Carola; Pérez-Alvarez, Daniel Kevin; Garcés-Elías, María Claudia; León-Manco, Roberto A. (COVID, 2024)
Subjective well-being (SW) is understood as the personal judgment that an individual has about their value, perception, and level of satisfaction with respect to his or her life and existence. The present study had the purpose of understanding how pandemics have affected subjective well-being; therefore, the objective was to determine the subjective well-being of the staff at a teaching dental center in a COVID-19 epidemiological surveillance system between the years 2020 and 2022. A cross-sectional design was applied and was based on data from two records of the Centro Dental Docente of the Universidad Peruana Cayetano Heredia, Lima, Peru, between the years 2021 and 2022. The results show that the mean SW did not significantly vary (p = 0.114) between 2021 (69.32; SD = 19.92) and 2022 (63.16; SD = 29.87). At a bivariate level, significant associations were also observed between SW and multiple variables such as the diagnosis and type of COVID-19, vaccination, contact with COVID-19 patients, systemic conditions, body mass index, educational level, gender, and age. Meanwhile, according to the regression analysis, not having COVID-19 was positively associated with higher levels of subjective well-being. This study highlights the impact of the COVID-19 pandemic on the mental and emotional states of dental healthcare personnel, emphasizing the need for strategies to mitigate stress and anxiety in such critical work environments.